Profile of HIV positive clients: an ICTC record based retrospective study - Dutt, Rekha; Chaudhuri, Susmita; Goswami, Shweta (International Journal Of Community Medicine And Public Health, 2017)
Background: Deaths in productive age group due to HIV/AIDS have damaging impact on families and communities, skills are lost, workforce shrinks & children’s are orphaned. Our study reports the socio-demographic characteristics of HIV/ AIDS clients from one of the Integrated Counselling & Testing Centre (ICTC) situated at Amtala, West Bengal. This will give us an insight on the distribution of various epidemiological characteristics of the HIV positive clients in this region thus help in formulating strategies for effective implementation of its prevention. The objective was to study socio-demographic profile and risk behavior pattern of HIV positive clients attending ICTC. Methods: It was an observational study cross sectional in design. Records of last eight years of HIV positive clients were accessed from ICTC centre at Amtala hospital, rural training centre, Department of community medicine, ESI PGIMSR medical college, Joka, Kolkata. Data was entered in SPSS for Windows version 20 software. Data was presented in percentages, mean with standard deviation etc. Results: Retrospective record of 62 HIV positive clients was studied, of them 37 were males (5 pediatric cases) and 25 females (7 ANC).Excluding pediatric clients, mean age of clients was 32 years. It was observed that majority of clients were illiterate and were on daily wages. Except one male client who was homosexual rest were heterosexual. Majority of clients 71.9% males and 92% females were married, of them 45.3% males and 34.7% females were sero concordant with their spouse. Seventeen subjects were co infected with TB. Conclusions: HIV sero prevalence rate has inverse relation with literacy level. Majority of male clients were daily wagers who act as link between high risk populations to general population i.e. their spouse, which in turn can pass on the infection to her baby. Lack of knowledge on mode of spread and preventive measures against HIV infection devastate the families making many children orphaned. There is need to carry out intense IEC activities for behavior change at grass root level.